Pengaruh Kreativitas dan Family Background Terhadap Intensi Berwirausaha Mahasiswa - Luthfianda, Naufal; Silvia, Armida (Universitas Negeri Padang, 2024)
This study's goal is to determine how students in Padang State University's Faculty of Languages and Arts Visual Communication Design Study Program perceive the impact of creativity and family history on their aspirations to pursue entrepreneurship. This study uses a quantitative method to investigate causal relationships. 560 students from the 2019–2022 class made up the study's population. Both primary and secondary sources of information were employed. An 85-person sample is subjected to a sampling method known as proportionate random sampling. Using the SPSS V.21 software, The method used for analysis is multiple linear regression analysis. To assess the research hypothesis, data were gathered using t statistical tests at a=0.05, normality testing, F tests, multicollinearity, heteroscedasticity, and validity tests at reliability tests. The study's conclusions show that: 1) inventiveness significantly influences the desire to start a business. 2) Ambition for entrepreneurship is influenced by family background 3) The desire to start one's own business is greatly influenced by one's ingenuity and family background.